PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA PANAS BUMI / GOETHERMAL ENERGY ( PLTPB ) - Moediyono, Moediyono (Vocational School Diponegoro University, 2010)
Moediyono, in paper development of electrical generator from geothermal energy explain that the growth of electric need which rapidly, where as the price of BBM more increasingly, so on several years can worry about the electric generator which have now, especially which using the fuel fossil can not fulfill he need of electric stock on consumen Then, it need reconstruction the electric generator whic will suitable with government wisdom in energy seetor with be hrifly on using of BBM, and remembered the back up of BBM in Indonesia which had more thin. One of alternative energi resorces which can used is geothermal that many in Indonesia broad. Geothermal energi electric generator have several superiorrty compare with electric generator another, among other does not reed the oil material, easy towalk with environment and also have operational time that relative more than long and does not influence the weather. Keyword: geothermal energy, generator, PLTB